Abrasive Water Jet Machining of Carbon Fiber-Reinforced PLA Composites: Optimization of Machinability and Surface Integrity for High-Precision Applications - Kartal, Fuat (MDPI AG, 2025)
Carbon fiber-reinforced polylactic acid (CFR-PLA) composites have emerged as a promising material for aerospace and automotive applications due to their superior mechanical strength and environmental sustainability. However, challenges such as surface irregularities and dimensional instability during machining have hindered their wider adoption. This study investigates the performance of abrasive water jet machining (AWJM) in optimizing the surface quality and machinability of CFR-PLA compared to pure PLA. Under optimal machining parameters (3500 bar water pressure, 800 mm/min traverse speed, and 250 g/min abrasive flow rate), CFR-PLA demonstrated a 23% reduction in surface roughness (Ra) and a 15% reduction in kerf taper angle (T) relative to pure PLA. These results highlight the stabilizing effect of carbon fiber reinforcement, which enhances dimensional accuracy and mechanical stability during machining. The findings position AWJM as an effective method for processing CFR-PLA, enabling its use in lightweight, high-precision applications such as aerodynamic components and structural prototypes. This study addresses a critical gap in the machinability of hybrid composites and provides actionable insights for sustainable manufacturing. Future research should explore hybrid reinforcement strategies, further parameter optimization, and advanced post-processing techniques to maximize CFR-PLA’s potential for demanding engineering applications.
Keywords: Article